2018
DOI: 10.1111/1556-4029.13741
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Approach to Assess the Biogeographical Patterns of Soil Communities: The Utility for Soil Provenance,

Abstract: Soil DNA profiling has potential as a forensic tool to establish a link between soil collected at a crime scene and soil recovered from a suspect. However, a quantitative measure is needed to investigate the spatial/temporal variability across multiple scales prior to their application in forensic science. In this study, soil DNA profiles across Miami-Dade, FL, were generated using length heterogeneity PCR to target four taxa. The objectives of this study were to (i) assess the biogeographical patterns of soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…Finally, the sample sites in this study were not only limited in number ( n = 10) and geographic location (i.e., only Virginia, USA), but also spatial and temporal variation. Given that previously published studies have identified that biological taxa can vary within a sample site (e.g., 10, 50, and 100 m apart), between seasons and across soil depths (e.g., [16,23,27,63,64]), additional studies designed to comprehensively assess the impact of these variables on sample separation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sample sites in this study were not only limited in number ( n = 10) and geographic location (i.e., only Virginia, USA), but also spatial and temporal variation. Given that previously published studies have identified that biological taxa can vary within a sample site (e.g., 10, 50, and 100 m apart), between seasons and across soil depths (e.g., [16,23,27,63,64]), additional studies designed to comprehensively assess the impact of these variables on sample separation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…plants, invertebrates) which can provide additional distinguishing features. As a result, the potential of eDNA for intelligence purposes to predict the origin of an unknown soil or dust sample [23][24][25]50], or even track the movements of an individual, has also been explored [36].…”
Section: Forensic Soil Sciencementioning
confidence: 99%
“…MiSAFE Project, a European initiative to standardise soil forensic DNA analysis involving 12 laboratories, also demonstrated that RISA and 16S MPS could both correctly affiliate a sample from a spade recovered from a suspect's home to the crime scene in the scenario. Furthermore, a number of studies have also incorporated temporal variation to demonstrate that profiles generated from soils collected weeks or months after a crime will likely be representative of the location where the soil transfer took place [19,21,50,54].…”
Section: Soil Comparisons For Evidential Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatic algorithms have simplified comparative genomics. Bioinformatics for medicine, microbial genome, and agriculture (Dahiya, 2017) are able to determine biologically relevant patterns in complex datasets (Damaso et al, 2018) as well as allow analyses of wholegenome shotgun sequencing of complex mixtures such as microbiomes (Citation: Chen and Pachter, 2005). The information derived from complex data will have to be extracted using algorithms such as support vector machines (Xu et al, 2015;Schlecht et al, 2008), neural networks Vidaki and Kayser, 2017), and other more complex algorithms yet to be developed.…”
Section: Bioinformaticsmentioning
confidence: 99%